Conversion of Unsaturated Short- to Medium-Chain Fatty Acids by Unspecific Peroxygenases (UPOs) - Alexander Karich; Fabian Salzsieder; Martin Kluge; Miguel Alcalde; René Ullrich; Martin Hofrichter (Applied Microbiology, 2023)
Eighteen short- to medium-chain monounsaturated fatty acids were screened for hydroxylation and epoxidation using eleven different peroxygenase preparations. Most of these unspecific peroxygenases (UPOs) are secreted by fungal species of the dark-spored basidiomycetous families Psathyrellaceae and Strophariaceae, two belonged to the white-spored genus Marasmius (Marasmiaceae), and one belonged to the ascomycetous family Chaetomiaceae. The fatty acids (FAs) studied were categorized into three groups based on the position of the double bond: (i) terminal unsaturated FAs (between ω and ω-1), (ii) α-β-unsaturated FAs (between C2 and C3), and (iii) β-γ-unsaturated FAs (between C3 and C4). Their chain lengths ranged from three to nine carbon atoms. FAs with a terminal double bond were significantly oxidized by only two UPOs, namely CglUPO and CraUPO (peroxygenases from Chaetomium globosum and Coprinellus radians, respectively), producing different products. FAs with internal double bonds were converted by all tested UPOs. While epoxides were observed as products in the case of α-β-unsaturated fatty acids, only CglUPO formed β-γ-epoxides from the corresponding FAs. The product pattern of the other UPOs for β-γ-unsaturated FAs was quite similar. On the other hand, the product pattern for oxidized α-β-unsaturated FAs was more variable and, in some cases, specific to a particular UPO. For example, in the reaction with trans-2-nonenoic acid, the enzymes clustered into six groups based on the formed products.